Integrasi Pengawasan Ruang Udara-Laut untuk Pengelolaan Perikanan Tangkap: Perspektif Hukum Udara dan Laut Internasional - Irma H. Hanafi; Welly A. Riry; Ifa T. Tazkira (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
This study examines the utilization of airspace for capture fisheries surveillance through an integrated perspective of international air law and the law of the sea. The increasing prevalence of illegal, unreported, and unregulated (IUU) fishing, coupled with the limitations of conventional sea-based patrol systems, necessitates more effective and adaptive monitoring approaches. Recent technological advancements, particularly the use of unmanned aerial vehicles (UAVs), offer significant potential for enhancing surveillance capacity; however, they also raise complex legal challenges. This research adopts a normative juridical approach, supported by conceptual and comparative analyses of the Chicago Convention and the United Nations Convention on the Law of the Sea. The findings reveal a fundamental normative fragmentation between the principle of complete and exclusive sovereignty over airspace and the concept of sovereign rights in maritime zones, particularly within the Exclusive Economic Zone (EEZ). This fragmentation creates legal uncertainty in the deployment of UAV-based surveillance systems. Furthermore, the study identifies a regulatory lag in international law, where existing legal frameworks have not kept pace with technological developments in multidomain monitoring systems. As a key contribution, this study proposes an integrated air–sea surveillance governance model based on the concept of functional sovereignty integration, which seeks to reconcile legal, technological, and institutional dimensions. This model provides both theoretical advancement in international law and practical policy implications for strengthening fisheries surveillance, particularly in archipelagic states such as Indonesia.